2015
DOI: 10.3389/fpls.2015.00709
|View full text |Cite
|
Sign up to set email alerts
|

Signaling in the phytomicrobiome: breadth and potential

Abstract: Higher plants have evolved intimate, complex, subtle, and relatively constant relationships with a suite of microbes, the phytomicrobiome. Over the last few decades we have learned that plants and microbes can use molecular signals to communicate. This is well-established for the legume-rhizobia nitrogen-fixing symbiosis, and reasonably elucidated for mycorrhizal associations. Bacteria within the phytomircobiome communicate among themselves through quorum sensing and other mechanisms. Plants also detect materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 125 publications
(152 reference statements)
0
40
0
3
Order By: Relevance
“…Altogether, this suggests that the high microbial diversity could have stimulated lateral root branching, thus enhancing root prospection in the soil and water perception by roots and leading to a higher stomatal conductance (see review by Blessing, Mariette, Kaloli, & Bramley, 2018). Some soil microbial species, known as plant growth promoting bacteria, secrete compounds able to modify root architecture (Mabood, Zhou, & Smith, 2014;Prudent, Salon, Souleimanov, Emery, & Smith, 2015;Smith, Subramanian, Lamont, & Bywater-Ekegärd, 2015) and lead to higher water and N uptake. In this study, although no evidence of microbial diversity impact was observed on the growth of 5-week-old wellwatered plants, the decrease in microbial diversity had important negative consequences on pea productivity, as revealed by the lower grain biomass produced by the plants.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, this suggests that the high microbial diversity could have stimulated lateral root branching, thus enhancing root prospection in the soil and water perception by roots and leading to a higher stomatal conductance (see review by Blessing, Mariette, Kaloli, & Bramley, 2018). Some soil microbial species, known as plant growth promoting bacteria, secrete compounds able to modify root architecture (Mabood, Zhou, & Smith, 2014;Prudent, Salon, Souleimanov, Emery, & Smith, 2015;Smith, Subramanian, Lamont, & Bywater-Ekegärd, 2015) and lead to higher water and N uptake. In this study, although no evidence of microbial diversity impact was observed on the growth of 5-week-old wellwatered plants, the decrease in microbial diversity had important negative consequences on pea productivity, as revealed by the lower grain biomass produced by the plants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, better appreciation of the phytomicrobiome [64,65] will help in increasing the understanding of crop cycles [66]. Knowing the mycotrophic status of plant species is an important piece of information for plant cultivation, ecological restoration, and for screening for plant stress tolerance.…”
Section: Redesigning Agro-ecosystems For Sustainabilitymentioning
confidence: 99%
“…Integrated crop-livestock systems can promote synergy between agricultural production and environmental quality mimicking the reality and diversity of natural rural systems [51,53]. In this context, the mycorrhizal fungi are crucial contributors of the phytomicrobiome (the complex plant associations with microbial communities [76]), and interactions with plant roots are also of importance in the rhizomicrobiome [64,66,77].…”
Section: Redesigning Agro-ecosystems For Sustainabilitymentioning
confidence: 99%
“…Smith et al [13] opined that the foundation of Natural Farming production lies in the health of the soil. A fertile soil provides essential nutrients to the growing crop and helps support a diverse and active biotic community.…”
Section: Role Of Natural Farming To Improve Pepper Cultivationmentioning
confidence: 99%
“…The important consideration here is the careful selection of a mixed culture of compatible, effective microorganisms properly cultured and provided with acceptable organic substrates [12,13]. In Natural Farming, these beneficial microorganisms can be grown to high populations and then applied to soils that also have a large stable population of beneficial microorganisms, especially facultative anaerobic bacteria [14].…”
Section: Soil Microflora Associated With Natural Farmingmentioning
confidence: 99%